2019
DOI: 10.1177/2167479519886118
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the “Racial Contradiction”: An Experimental Examination of the Impact of Sports Media Use and Response Strategy on Racial Bias Towards Athlete Transgressors

Abstract: Previous studies have found that minority athletes were perceived more positively than their White counterparts, which is counterintuitive to previous research. In order to explain this “racial contradiction,” this study analyzes how an athlete's response strategy and the amount of sports news consumed by participants could impact differences in the perceptions of athletes of different races. A between-subjects, double-blind experiment was conducted among 464 participants to examine how an athlete’s race, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…This is important because it may be assumed that Black athletes would be perceived as more responsible, due to past research on Black individuals being seen as criminals (e.g., Mastro et al, 2011). However, the findings of this study suggest that Black athletes were not perceived as more responsible, which is again in support of the racial contradiction (Brown et al, 2015, 2016, 2019). Furthermore, audiences perceived athletes as equally responsible regardless of the sport.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This is important because it may be assumed that Black athletes would be perceived as more responsible, due to past research on Black individuals being seen as criminals (e.g., Mastro et al, 2011). However, the findings of this study suggest that Black athletes were not perceived as more responsible, which is again in support of the racial contradiction (Brown et al, 2015, 2016, 2019). Furthermore, audiences perceived athletes as equally responsible regardless of the sport.…”
Section: Discussionsupporting
confidence: 72%
“…RQ 1 found that perceived severity of the news story differed based on the race of the athlete involved but not based on the nature of the sport. These findings largely supported the “racial contradiction” (Brown et al, 2015, 2016, 2019) when it came to news story severity. In other words, violence carried out by White athletes was rated as more severe than violence carried out by Black athletes.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations